(3dZR GdgQe GdCcHQs - (3cQje, SjOs; (3EHQGgje, OGdjG eMeOs ((3GdbGgQgs (3fgVI eUQ ddWHGYI hGdfTQs, 2001)
(3h QHeG cGfJ TgQI GdgQe GdcHQ h eG OGQ MhdI ef GdCSGWjQ GdJi CZQb HYVgG ai GdNjGd CMO CSHGH XghQ gPG GdcJGH deG jMed ef JUMjM ddeaGgje GdJGQjNjI h YQV dCSQGQ LOjOI JfTQ dChd eQI Yf gPG GddZR GdcHjQ ai MjGI GdaQGYfIs
1 2 6 7 12
Keywords: (3eUQ GdbOjeIs -- (3JGQjNs; (3eUQs -- (3GdBKGQ GdaQYhfjIs; (3eUQ GdaQYhfjIs